SNX17 protects the heart from doxorubicin-induced cardiotoxicity by modulating LMOD2 degradation. (July 2021) - Zhang, Yanping; Ni, Le; Lin, Bowen; Hu, Lingjie; Lin, Zheyi; Yang, Jian; Wang, Jinyu; Ma, Honghui; Liu, Yi; Yang, Jian; Lin, Jianghua; Xu, Liang; et al.
Abstract: Anthracyclines including doxorubicin (DOX) are still the most widely used and efficacious antitumor drugs, although their cardiotoxicity is a significant cause of heart failure. Despite considerable efforts being made to minimize anthracycline-induced cardiac adverse effects, little progress has been achieved. In this study, we aimed to explore the role and underlying mechanism of SNX17 in DOX-induced cardiotoxicity. We found that SNX17 was downregulated in cardiomyocytes treated with DOX both in vitro and in vivo. DOX treatment combined with SNX17 interference worsened the damage to neonatal rat ventricular myocytes (NRVMs). Furthermore, the rats with SNX17 deficiency manifested increased susceptibility to DOX-induced cardiotoxicity (myocardial damage and fibrosis, impaired contractility and cardiac death). Mechanistic investigation revealed that SNX17 interacted with leiomodin-2 (LMOD2), a key regulator of the thin filament length in muscles, via its C-TERM domain and SNX17 deficiency exacerbated DOX-induced cardiac systolic dysfunction by promoting aberrant LMOD2 degradation through lysosomal pathway. In conclusion, these findings highlight that SNX17 plays a protective role in DOX-induced cardiotoxicity, which provides an attractive target for the prevention and treatment of anthracycline induced cardiotoxicity. Graphical Abstract: ga1